Production of nisin Z using Lactococcus lactis IO-1 from hydrolyzed sago starch - Octavio, Carvajal-Zarrabal; Cirilo, Nolasco-Hipolito; Kopli, Bujang; Ayaaki, Ishizaki (Springer Berlin Heidelberg, 2009)
A membrane bioreactor for production of nisin Z was constructed using Lactococcus lactis IO-1 in continuous culture using hydrolyzed sago starch as carbon source. A strategy used to enhance the productivity of nisin Z was to maintain the cells in a continuous growth at high cell concentration. This resulted in a volumetric productivity of nisin Z, as 50,000 IU l-1 h-1 using a cell concentration of 15 g l-1, 30 C, pH 5.5 and a dilution rate of 1.24 h-1. Adding 10 g l-1 YE and 2 g l-1 polypeptone, other inducers were unnecessary to maintain production of nisin. The operating conditions of the reactor removed nisin and lactate, thus minimizing their effects which allowed the maintenance of cells in continuous exponential growth phase mode with high metabolic activity.